2023
DOI: 10.3390/plants12173134
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Soybean and Cowpea Cultivars with Superior Performance under Drought Using Growth and Biochemical Aspects

Rafael de Souza Miranda,
Bruno Sousa Figueiredo da Fonseca,
Davielson Silva Pinho
et al.

Abstract: Identifying cultivars of leguminous crops exhibiting drought resistance has become crucial in addressing water scarcity issues. This investigative study aimed to select soybean and cowpea cultivars with enhanced potential to grow under water restriction during the vegetative stage. Two parallel trials were conducted using seven soybean (AS3810IPRO, M8644IPRO, TMG1180RR, NS 8338IPRO, BMX81I81IPRO, M8808IPRO, and BÔNUS8579IPRO) and cowpea cultivars (Aracê, Novaera, Pajeú, Pitiúba, Tumucumaque, TVU, and Xique-xiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In a preliminary study under greenhouse conditions, we challenged seven soybean genotypes (AS3810 IPRO, M8644 IPRO, TMG 1180, NS8338 IPRO, BMX 81I81, M8808 IPRO and Bo ˆnus 8579) to several drought treatments to choose the most drought-contrasting genotypes. Based on plant growth and indicators of stress tolerance, we observed that M8808 is droughtsensitive; Bo ˆnus 8579 is tolerant to moderate drought and discreetly tolerant to severe stress; and TMG is highly tolerant to drought [27]. In the current study, field experiments were carried out to evaluate the role of Mg supplementation in triggering water stress acclimation in drought-sensitivity contrasting soybean genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…In a preliminary study under greenhouse conditions, we challenged seven soybean genotypes (AS3810 IPRO, M8644 IPRO, TMG 1180, NS8338 IPRO, BMX 81I81, M8808 IPRO and Bo ˆnus 8579) to several drought treatments to choose the most drought-contrasting genotypes. Based on plant growth and indicators of stress tolerance, we observed that M8808 is droughtsensitive; Bo ˆnus 8579 is tolerant to moderate drought and discreetly tolerant to severe stress; and TMG is highly tolerant to drought [27]. In the current study, field experiments were carried out to evaluate the role of Mg supplementation in triggering water stress acclimation in drought-sensitivity contrasting soybean genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, XiNong 9943, QianKu-5, and XiNong 9940 genotypes demonstrated a greater ability to withstand drought, as evidenced by their reduced shoots and roots length reductions and biomass accumulation in comparison to other cultivars. Several previous studies demonstrated that genotypes with elongated shoots and roots lengths [24,44], and lesser reductions in seedling water content and biomass accumulation [45,46] under drought stress conditions are essential for sustainable agricultural practices. These results emphasize the importance of identifying and selecting genotypes with superior drought tolerance traits to enhance crop productivity in water-stressed environments.…”
Section: Discussionmentioning
confidence: 99%
“…Specific endophytes can improve the resistance of pepper [4] and tomato [5] plants to biotic or abiotic stresses. Miranda et al [6] identified soybean and cowpea cultivars with superior performance under drought. Aziz et al [7] revealed the critical involvement of glycolysis, fermentation, and alternative oxidase to salt stress tolerance in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The articles published in this SI covered the identification and characterization of transcription factors associated with stress resistance [1][2][3], beneficial endophytic/plant interaction [4,5], and molecular mechanisms involved in crops and fruit plants to stress tolerance [6][7][8][9][10][11].…”
Section: Overview Of Simentioning
confidence: 99%
See 1 more Smart Citation